Computational Systems Pharmacology, Molecular Docking and Experiments Reveal the Protective Mechanism of Li-Da-Qian Mixture in the Treatment of Glomerulonephritis - Zhou W; Sha Y; Zeng J; Zhang X; Zhang A; Ge X (Dove Medical Press, 2021)
Wei Zhou,1,2,* Yugen Sha,2,* Jingxia Zeng,3,* Xiaoyue Zhang,4 Aihua Zhang,1,2 Xuhua Ge1,3 1Nanjing Key Laboratory of Pediatrics, Children's Hospital of Nanjing Medical University, Nanjing, People's Republic of China; 2Department of Nephrology, Children's Hospital of Nanjing Medical University, Nanjing, People's Republic of China; 3Pediatric Intensive Care Unit, Children's Hospital of Nanjing Medical University, Nanjing, People's Republic of China; 4Department of Chinese Medicine, The First Affiliated Hospital  of  Anhui  University  of  Chinese  Medicine, Hefei, People's Republic of China*These authors contributed equally to this workCorrespondence: Xuhua GePediatric Intensive Care Unit, Children's Hospital of Nanjing Medical University, 72 Guangzhou Road, Nanjing, 210029, People's Republic of ChinaEmail gexuhua@njmu.edu.cnAihua ZhangDepartment of Nephrology, Children's Hospital of Nanjing Medical University, 72 Guangzhou Road, Nanjing, 210029, People's Republic of ChinaEmail zhaihua@njmu.edu.cnBackground: Glomerulonephritis is a common urinary system disease among children. Growing evidence suggests that traditional Chinese medicine has potential in treating glomerulonephritis, such as Li-Da-Qian mixture. Although its anti-glomerulonephritis and alleviating hematuria effects have been reported, the exact mechanism of Li-Da-Qian mixture devoting to glomerulonephritis remains unexplored. It was necessary to explore the mechanism of Li-Da-Qian mixture against glomerulonephritis using modern technology, such as Chinese medicine database and molecular biological experiments.Methods: Online databases were used to look up ingredients and predict targets of Li-Da-Qian mixture against glomerulonephritis. The intersecting targets of Li-Da-Qian mixture and glomerulonephritis were selected for enrichment analysis. Cytoscape software was applied to establish network and MCODE analysis. Molecular docking was used for the primary validation. Furthermore, we examined the function of the core compounds analyzed from Li-Da-Qian mixture to rescue LPS-induced inflammation in vivo and vitro. We also explored whether the core compounds can alleviate TGFβ 1-induced renal fibrosis in mouse proximal tubular cells.Results: Network pharmacological analysis of Li-Da-Qian evaluated 20 active ingredients including baicalein, luteolin and quercetin. A total of 113 key targets were screened, including IL6, VEGFA, TP53, EGF, MMP2, etc, and they were enriched in AGE-RAGE signaling pathway in diabetic complications, TNF and IL-17 signaling pathways. Moreover, the core ingredients succeeded in binding to the main targets via molecular docking, further identifying the anti-glomerulonephritis effects and improvement of vascular injury. Western blotting and qPCR also suggested that baicalein and luteolin can improve inflammation and restore disturbance of mesangial cells or kidney induced by LPS. In addition, baicalein and luteolin inhibited renal fibrosis in vitro.Keywords: glomerulonephritis, network pharmacology, Li-Da-Qian mixture, traditional Chinese medicine, molecular docking